2012
DOI: 10.1100/2012/482575
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Abnormalities Caused by HIV-1 gp120: Mechanistic and Therapeutic Implications

Abstract: The blood-brain barrier (BBB) is compromised in many systemic and CNS diseases, including HIV-1 infection of the brain. We studied BBB disruption caused by HIV-1 envelope glycoprotein 120 (gp120) as a model. Exposure to gp120, whether acute [by direct intra-caudate-putamen (CP) injection] or chronic [using SV(gp120), an experimental model of ongoing production of gp120] disrupted the BBB, and led to leakage of vascular contents. Gp120 was directly toxic to brain endothelial cells. Abnormalities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 81 publications
(112 reference statements)
1
50
0
Order By: Relevance
“…Early exercise studies in PLWH contained mostly male participants (Rigsby, Dishman, Jackson, MacLean, & Raven, 1992;MacArthur, Levine, & Birk, 1993;Lox, McAuley, & Tucker, 1995;Sattler et al, 1999, Bhasin et al, 2000. All but three of the studies in this review had a signifi cantly higher proportion of male to female participants, with as little as 13% females in one study (Smith et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Early exercise studies in PLWH contained mostly male participants (Rigsby, Dishman, Jackson, MacLean, & Raven, 1992;MacArthur, Levine, & Birk, 1993;Lox, McAuley, & Tucker, 1995;Sattler et al, 1999, Bhasin et al, 2000. All but three of the studies in this review had a signifi cantly higher proportion of male to female participants, with as little as 13% females in one study (Smith et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…The pathophysiology of the mechanisms of how viral RNA is integrated into immune and tissue cells continues to be an exciting fi eld for discovery (Louboutin & Strayer, 2012). The HIV virus, on the other hand, has never been known to infect skeletal or cardiac myocytes directly (Otis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, gp120 can induce the degradation of tight junction proteins in human brain microvascular endothelial cells and has been associated with increased permeability of the blood brain barrier (BBB) during progressive HIV-1-associated dementia (25)(26)(27)(28)(29). The enhanced BBB permeability induced by HIV-1 gp120 has also been observed in transgenic mice (26,30). Treatment with HIV-1 gp120 down-regulated the expression of tight junction proteins in human RPE cells and led to increased monolayer permeability and consequent translocation of HIV-1 and bacteria across the epithelium (31).…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Other studies revealed that direct contact of HIV-1 with the endothelium, which share tight junction structures in common with the epithelium, [17][18][19] could lead to the disruption of endothelial integrity and subsequent increased viral leakage across the endothelium. HIV-1 gp120 and Tat protein have been associated with the disruption of tight junctions in the endothelium.…”
mentioning
confidence: 99%